Epistemologi Penelitian Pendidikan: Telaah Teoretis atas Ruang Lingkup dan Fungsinya dalam Pendidikan Modern - Gerry Mandala (MAN 4 Kota Pekanbaru, 2025)
This literature based study examines the epistemology of educational research by addressing the central question: how do the epistemological scope and functions of research shape the development of contemporary educational science? The analysis focuses on three epistemological dimensions the nature of knowledge, sources of validity, and modes of scientific justification. The study employs a structured literature review with selection criteria that include open-access articles published between 2020 and 2025, relevance to epistemology and educational research methodology, and the presence of theoretically substantive findings. The review indicates that epistemological foundations significantly influence research orientation, methodological coherence, and the strength of scientific argumentation in both theory-building and educational practice. The conceptual contribution of this study lies in mapping the linkage between epistemic structures and the core functions of research from theory development and problem-solving to policy formulation thus reinforcing an integrative and reflective paradigm for modern education.